Upaya Pemenuhan Kebutuhan Seksual Warga Binaan Pemasyarakatan Guna Mencegah Penyimpangan Seksual di Dalam Lembaga Pemasyarakatan Sesuai Dengan Standard Minimum Rules - Yurike Violina (Universitas Batanghari Jambi, 2021)
The sexual needs of prisoners become one of the problems in Penitentiary because there are no clear rules that cause prisoners anxiety so that there are many sexual deviations that occur in the Penitentiary. The biological needs of prisoners must be met by the State because they are also included in international instruments Standard Minimum Rules for the Treatment of Prisoners. The fulfilment of prisoners rights is regulated in Law No. 12 of 1995 concerning Penitentiary where detainees only lose their freedom but do not lose their rights and dignity as human beings.